(untitled) - Lathi, B. P. (New York, 2019)
As engineering students become more and more aware of the important role that communication systems play in modern society, they are increasingly motivated to learn through experimenting with solid, illustrative examples. To captivate students' attention and stimulate their imaginations, Modern Digital and Analog Communication, Fifth Edition, places strong emphasis on connecting fundamental concepts of communication theory to students' daily experiences of communication technologies. The text provides highly relevant information on the operation and features of wireless cellular systems, Wi-Fi access, broadband Internet services, and more.
Keywords: Giao tiếp số,Digital communications